2012
DOI: 10.1073/pnas.1206834109
|View full text |Cite
|
Sign up to set email alerts
|

Altered fear learning across development in both mouse and human

Abstract: The only evidence-based behavioral treatment for anxiety and stress-related disorders involves desensitization techniques that rely on principles of extinction learning. However, 40% of patients do not respond to this treatment. Efforts have focused on individual differences in treatment response, but have not examined when, during development, such treatments may be most effective. We examined fear-extinction learning across development in mice and humans. Parallel behavioral studies revealed attenuated extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
423
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(481 citation statements)
references
References 57 publications
32
423
8
Order By: Relevance
“…It has been suggested that an enhanced glutamatergic input from the IL-mPFC activates amygdala neurons particularly the GABAergic neurons in the intercalated cell masses and suppresses the centromedial amygdala output and fear response (Ninan, 2014;Pare et al, 2004). Consistently, the IL-mPFC glutamatergic synapses undergo potentiation during fear extinction (Pattwell et al, 2012b;Sepulveda-Orengo et al, 2013). To understand whether endogenous estradiol modulates the IL-mPFC synapses, we studied glutamatergic synaptic transmission and plasticity in the IL-mPFC layer 5 pyramidal neurons, the major projection neurons (Gabbott et al, 2005), from proestrus (high estradiol) and diestrus (low estradiol) mice (Spencer et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…It has been suggested that an enhanced glutamatergic input from the IL-mPFC activates amygdala neurons particularly the GABAergic neurons in the intercalated cell masses and suppresses the centromedial amygdala output and fear response (Ninan, 2014;Pare et al, 2004). Consistently, the IL-mPFC glutamatergic synapses undergo potentiation during fear extinction (Pattwell et al, 2012b;Sepulveda-Orengo et al, 2013). To understand whether endogenous estradiol modulates the IL-mPFC synapses, we studied glutamatergic synaptic transmission and plasticity in the IL-mPFC layer 5 pyramidal neurons, the major projection neurons (Gabbott et al, 2005), from proestrus (high estradiol) and diestrus (low estradiol) mice (Spencer et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…The IL-mPFC-mediated top-down regulation of the amygdala, a mechanism believed to control fear extinction, involves synaptic potentiation in the IL-mPFC (Pare et al, 2004;Pattwell et al, 2012b;Sepulveda-Orengo et al, 2013). Therefore, the estradiol-dependent facilitation of synaptic potentiation in the IL-mPFC might contribute significantly to the enhancement of fear extinction (Chang et al, 2009;Zeidan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paralleling the influence of stress on the maturation of fear learning, separation from the mother advances the onset of adult-like extinction learning, from which fears reemerge (Callaghan and Richardson, 2011). In contrast to the ease with which fears are diminished in these younger animals, both fear extinction learning and retention are attenuated during adolescence (Kim et al, 2011;McCallum et al, 2010;Pattwell et al, 2012). Relative to pre-and post-adolescent animals, adolescents exhibit diminished fear extinction learning that is paralleled by an absence of fear-learning-induced synaptic plasticity within the PL and extinction-learning-induced plasticity within the IL .…”
Section: Developmental Changes In Fear-learning Circuitsmentioning
confidence: 99%
“…This is important, because different types of traumatic exposure have differential effects on outcome (Brewin, Andrews, & Valentine, 2000). Trauma occurring in early life may have particularly strong effects on neurocognitive function given the multiple developmental changes in the brain that are occurring and the subsequent effects on extinction learning (Caspi et al, 2003; Gould et al, 2012; Pattwell et al, 2012; Slopen, Koenen, & Kubzansky, 2014). Animal studies have shown that early life stress permanently affects extinction learning and fear-related memory (Chocyk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%